An assessment of the training needs in information technology among academic librarians in Metro Manila - Olid, Jocelyn G.; Salang, Ma. Maura M.; Cruz, Ma. Divina P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
This study was conducted to find out the training needs in Information Technology (IT) of academic librarians in Metro Manila. The one hundred sixty five (165) professional licensed academic librarians who are members of the 1996 Philippine Librarians Association, Inc. (PLAI) were the respondents of the study. The descriptive method was used with questionnaire as the main data-gathering tool, supplemented by interviews, observation and examination of records.
Data obtained from the study revealed that the academic librarians still lack competence in using computers in library operations. A lot of training programs in Information Technology (IT) application to library operations should be conducted.
Results of the study showed that they really need intensive training on networking, surfing the internet, hardware maintenance and troubleshooting, automated cataloging, operating system, system analysis and design, management of library automation system, homepage creation, digital electronics, telecommunication, database creation and management, multimedia design and application, e-mail, file transfer, and desktop publishing. Academic librarians also need intensive training on application softwares, specifically on word processing, spreadsheet, database management and presentation software. Hands-on training is the most recommended training method. Other recommendations formulated are based on the revealed individual needs of academic librarians.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library education -- Philippines -- Manila Metropolitan Area; Academic libraries -- Philippines -- Manila Metropolitan Area; Librarians -- Philippines -- Manila Metropolitan Area